Persepsi Mahasiswa Terhadap Penggunaan Media Digital Dalam Pembelajaran Bahasa Arab - Baiq Raudatussolihah (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The development of digital technology has significantly impacted the learning process in higher education, including Arabic language learning. This study aims to describe the perceptions of students in the Arabic Language Education Study Program at Makassar State University regarding the use of digital media in Arabic language learning. The study used a descriptive quantitative approach with a survey method. The research subjects consisted of 60 students in the Arabic Language Education Study Program at Makassar State University. Data collection techniques were conducted through a Likert-based questionnaire and limited interviews. The results showed that the majority of students had a positive perception of the use of digital media in Arabic language learning. Digital media is considered capable of increasing learning motivation, facilitating material understanding, expanding access to learning resources, and helping improve Arabic language skills, especially maharah istima' and kalam. In addition, the use of digital media also creates a more interactive and flexible learning atmosphere. However, the study found several obstacles such as limited internet connection, social media distractions, and differences in students' digital literacy skills. Therefore, appropriate learning strategies are needed so that the use of digital media can take place effectively and optimally in Arabic language learning in higher education.